Variability and Correlations Among Growth Attributes in Sapota - Viswanath, P; Al-Gabry, M; Nadaf, S K (Annals of Arid Zone, 2016)
The data on growth attributes, of four-year-old pre-bearing sapota (Acinus zapota L.) trees planted in 1991 at the experimental orchard of Agriculture Research Center, Rumais, Sultanate of Oman, were subjected to analysis of variability and correlations. Among the five growth attributes studied, canopy volume had the highest range of variability (16.70 to 47.50 m3) followed by E-W spread (2.90 to 4.40 m), tree height (2.06 to 3.44 m), N-S spread (2.90 to 4.40 .m) and trunk girth (0.230 to 0.380 cm). Of the fifteen character associations (r values), the correlations associated with the canopy volume were found to be positive and significant, which could be used in predicting behavior of plant in terms of it's future growth and development.